The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1057/s41264-023-00235-7
|View full text |Cite
|
Sign up to set email alerts
|

Big data analytics and innovation in e-commerce: current insights and future directions

Abstract: Big data analytics (BDA), as a new innovation tool, played an important role in helping businesses to survive and thrive during great crises and mega disruptions like COVID-19 by transitioning to and scaling e-commerce. Accordingly, the main purpose of the current research was to have a meaningful comprehensive overview of BDA and innovation in e-commerce research published in journals indexed by the Scopus database. In order to describe, explore, and analyze the evolution of publication (co-citation, co-autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 144 publications
0
4
0
Order By: Relevance
“…Chinna et al [ 42 ] and Sobaih et al [ 9 ] have shown that the inclusion of students and faculty members facilitates the utilization of social media for official academic functions. Students perceived social media as a more efficacious means of communication compared to other cost-free online communication platforms such as Google Classroom and Zoom, owing to its ease of use, usefulness, and engagement [ 43 ]. Consequently, they leveraged social media to facilitate the process of learning.…”
Section: Discussionmentioning
confidence: 99%
“…Chinna et al [ 42 ] and Sobaih et al [ 9 ] have shown that the inclusion of students and faculty members facilitates the utilization of social media for official academic functions. Students perceived social media as a more efficacious means of communication compared to other cost-free online communication platforms such as Google Classroom and Zoom, owing to its ease of use, usefulness, and engagement [ 43 ]. Consequently, they leveraged social media to facilitate the process of learning.…”
Section: Discussionmentioning
confidence: 99%
“…Decision-making is considered an important factor that affects the success and efficiency of e-commerce processes [17]. In recent years, researchers have explored various approaches and technologies to support decision-making in the e-commerce domain [18]. This section examines key studies that highlight the significance of decision-making in e-commerce processes and the technologies used to enhance decisionmaking capabilities.…”
Section: Technologies That Enhance Decision-making In E-commerce Proc...mentioning
confidence: 99%
“…Furthermore, blockchain enables the automation of accounting processes through smart contracts, eliminating the need for intermediaries and reducing errors. Overall, blockchain technology revolutionizes digital accounting by enhancing transparency, security, efficiency and trust in financial transactions (Alsmadi et al, 2023a(Alsmadi et al, , 2023b(Alsmadi et al, , 2023cSingh et al, 2023;Yoon, 2020). Moreover, the exact consequences of digital transformation in the field of accounting remain uncertain.…”
Section: Introductionmentioning
confidence: 99%